INSTRUMENTOS DE PARTICIPAÇÃO POPULAR NO DESENVOLVIMENTO DE POLÍTICAS DEMOCRÁTICAS (Reflection and Critique Law Magazine, 2024)
This article discusses the relevance of popular participation in the process of strengthening Brazilian democracy. The debate on the crisis of democracy that dominated the world in the last decade also affects Brazilian democracy, and in this sense it is necessary to find ways not only to maintain, but to strengthen democracy in Brazil. Although the Brazilian Federal Constitution presents incentives and instruments for participation, the reality of popular participation is still timid. Traditional instruments of participation can be rediscovered and strengthened, as well as it is necessary to find new instruments of participation that adapt to the reality of the new times, avoiding the risks of participation and building a democracy of popular participation. This article is developed through bibliographical research and investigations on possible instruments of participation.